Open Skies The National Radio Astronomy Observatory and Its Impact on US Radio Astronomy - Kellermann, Kenneth I.; Bouton, Ellen N.; Brandt, Sierra S. (Historical & Cultural Astronomy,, 2020)
This open access book on the history of the National Radio Astronomy Observatory covers the scientific discoveries and technical innovations of late 20th century radio astronomy with particular attention to the people and institutions involved. The authors have made extensive use of the NRAO Archives, which contain an unparalleled collection of documents pertaining to the history of radio astronomy, including the institutional records of NRAO as well as the personal papers of many of the pioneers of U.S. radio astronomy. Technical details and extensive citations to original sources are given in notes for the more technical readers, but are not required for an understanding of the body of the book. This book is intended for an audience ranging from interested lay readers to professional researchers studying the scientific, technical, political, and cultural development of a new science, and how it changed the course of 20th century astronomy.